2016
DOI: 10.1016/j.jef.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the relationships between local foods and residents: A case in the Noto region, Japan

Abstract: Article history: Available online xxx Keywords: food producer knowledge transmission local environment local food satoyama social network a b s t r a c t Q 3Through an analysis of the Noto peninsula, we explore the relationships between the attributes of local food producers and the variety of foods they produce, attempting to identify the key attributes related to making diverse local foods and the transmission of local food knowledge. Our analysis showed a correlation between the diversity of local foods mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It is in line with the research conducted by Kohsaka et al, 2016 who studied local food in Japan. He stated that people who live longer has the experience and ability to introduce local food diversity to other residents and spreading through social network.…”
Section: Factors Affecting Sikkato Consumptionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is in line with the research conducted by Kohsaka et al, 2016 who studied local food in Japan. He stated that people who live longer has the experience and ability to introduce local food diversity to other residents and spreading through social network.…”
Section: Factors Affecting Sikkato Consumptionsupporting
confidence: 88%
“…Husain (2004) stated that local food was a food produced in the local area for the purposes of economic and or consumption determined by the distance between production site and consumption area (Feldmann and Hamm, 2015) involving local resident (Kohsaka et al, 2016) including friends, relatives, and neighbors (Feldmann and Hamm, 2015 …”
Section: Local Food Of Sikkatomentioning
confidence: 99%
“…Studies have shown that the transmission of indigenous knowledge across generations is key in preserving the knowledge, attitudes, practices, and perceptions around these foods [ 41 ]. In certain countries and cultures, documentation has been astute to preserve the heritage around these foods [ 41 43 ]. We recommend the same for Zimbabwe traditional foods.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of this study, a brewery and a farmer regarded the experience of long-term transactions and agreed to the price assuming the future transactions. Like this, the breweries could devise the strategies to align the production of organic sake in line with the enhancement of its competitiveness through terroir [1,19,23,24]. This could make the local breweries of organic sake gain some edge against national and transnational breweries.…”
Section: Discussionmentioning
confidence: 99%